If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 8 = 64 Reorder the terms: 8 + 8y = 64 Solving 8 + 8y = 64 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 8y = 64 + -8 Combine like terms: 8 + -8 = 0 0 + 8y = 64 + -8 8y = 64 + -8 Combine like terms: 64 + -8 = 56 8y = 56 Divide each side by '8'. y = 7 Simplifying y = 7
| 6r^2-9=3 | | G-5=-9 | | 2+-6=y | | a^2-10=50 | | 1x+5=13 | | -10x^2=-360 | | x-8.1=-6.9 | | x+33=24 | | n^2-3=46 | | 9y-1=80 | | 10x-2=-72 | | 10x+15=95 | | 5x+32=x | | n^2=46 | | 5+2h=20 | | -72-3(-9-4)=3(-9-4)+6 | | 5y-5=10 | | 8x-3(x-4)=3(x-4)+6 | | 2y-7=9 | | y=4x+3whatisy | | 3x-2(2+5)=2(x+3)-8 | | 10x+14=34 | | -5x+5=10 | | y=3+4x | | -10x+6=26 | | -x+4y=3 | | 5v-20=25 | | 3x+4=5x+4 | | 1.5x=x+1.5 | | 3y^3-6xy+2x^3=-1.26 | | 6x+84=3x-12 | | (3d-4)/6+1=(d+1)/8 |